2013
DOI: 10.1177/1075547013491398
|View full text |Cite
|
Sign up to set email alerts
|

Research Utilization in the Social Sciences

Abstract: Social science disciplines generate diverse forms of research utilization, given the various contexts in which disciplinary knowledge is produced and translated for the fields of policy and practice. We examine this issue from the perspective of academic researchers in the social sciences across education, economics, sociology, political science, and psychology. We use survey data from a study of university-based social science researchers in Australia to examine factors that influence perceptions of the polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…While not strong, there was a positive relationship between whether respondents reported they used quantitative approaches and subsequent utilisation. Landry et al (2001aLandry et al ( , 2001b found a similar result in relation to particular social science disciplines, as did Cherney and McGee (2011) and Cherney et al (2013). It is possible that the perceived effect of quantitative methods in influencing levels of utilisation may reflect the preferences and bias of users for particular types of research.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…While not strong, there was a positive relationship between whether respondents reported they used quantitative approaches and subsequent utilisation. Landry et al (2001aLandry et al ( , 2001b found a similar result in relation to particular social science disciplines, as did Cherney and McGee (2011) and Cherney et al (2013). It is possible that the perceived effect of quantitative methods in influencing levels of utilisation may reflect the preferences and bias of users for particular types of research.…”
Section: Discussionmentioning
confidence: 72%
“…We use a similar approach to that adopted in the study by Landry et al (2001aLandry et al ( , 2001b and draw on the Knott and Wildavsky (1980) research-use scale to examine factors that appear to influence reported levels of research impact. We do not examine knowledge utilisation rates between specific social science disciplines (see Cherney et al, 2013, for a comparison across sociology, education, psychology, economics and political science). While we recognise that different scientific disciplines may generate diverse forms of utilisation, given that the various contexts in which knowledge is produced and processed vary across research domains, our aim here is to generate broader generalisations about knowledge utilisation in the social sciences.…”
mentioning
confidence: 99%
“…It is thus premature to conclude that broad changes have eroded the traditions and local contexts of specific disciplines and research units. There remains a multiplicity of research practices in academia; researchers are active actors who regulate their responses to change according to their values, interests, objectives and traditions (Cherney et al 2013;Goodall 2009).…”
Section: Changes In Knowledge Production Across Research Contextsmentioning
confidence: 99%
“…Partnerships in which university researchers work directly on a non-university actor's practical problem increase the likelihood that research solutions will be adopted (Cherney, Head, Boreham, Povey, & Ferguson, 2013;Lindblom & Cohen, 1979) over more passive strategies that assume that if researchers produce relevant research other actors will take it up. Partnering on a real world problem ensures that researchers work on problems relevant to partners with those partners, who are often also solution adopters.…”
Section: Lessons For Encouraging More Solution-oriented Social and Bementioning
confidence: 99%